Features of adaptive brake control of the secondary brake system of a multi-axle vehicle - Bogomolov, V. O.; Klimenko, V. I.; Leontiev, D. M.; Kuripka, O. V.; Frolov, A. A.; Don, E. Yu.; Богомолов, В. О.; Клименко, В. І.; Леонтьєв, Д. М.; Куріпка, О. В.; Фролов, А. А.; Дон, Є. Ю. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. Malfunction of the service braking system of a wheeled vehicle (WV) significantly affects road safety, especially when operating multi-axle vehicles with big masses. One of the ways to increase the level of road safety of multi-axle vehicles, when braking using a spare (emergency) braking system, is the introduction of automated adaptive braking systems into the design of the brake drive of vehicles. The definition of the limits of using the adaptive braking system on vehicles with many axles is almost not disclosed in the scientific and technical literature, therefore, the issue of using such a system on vehicles with a large number of axles requires additional research. Purpose. The purpose of this work is to develop a simulation model for adaptive control of the braking process of a multi-axle vehicle using a spare (emergency) braking system, taking into account the simulation of the dynamics of the drive and the variability of the adhesion properties between the tire of the vehicle wheel and the road surface. Methodology. To achieve this goal, it is necessary to develop a simulation model of the brake drive in an adaptive mode, implement a model of the interaction of the tire with the road surface, and implement a model of the braking dynamics of a multi-axle vehicle in the event of a malfunction of its service brake system. Originality. The proposed key criterion (Kr) for changing the throttle section in electro-pneumatic pressure modulators, which provide adaptive air inlet or outlet from the corresponding brake chambers of the drive, during simulation, made it possible to simulate the operation of the drive circuits in the adaptive mode. It has been established that, depending on the potential for the realization of the adhesion between the tires of automobile wheels and the road surface, the pressure in the electro-pneumatic brake drive with its adaptive regulation can be increased by no more than 0.04 MPa.
Особливості адаптивного управління гальмом запасної гальмової системи багатовісного автомобіля
Keywords: brake control; multi-axle vehicle; adaptive control; braking; secondary brake system; emergency braking; adhesion utilized by axle; керування гальмами; багатовісний транспортний засіб; адаптивне керування; гальмування; запасна (аварійна) гальмівна система; екстрене гальмування; реалізоване зчеплення; 629.113; 10.30977/AT.2219-8342.2021.48.0.27